Pengaruh Content Marketing terhadap Keputusan Pembelian Produk Skincare Glad2glow di Marketplace Tiktok Shop - Jinan, Farodisal; Nury Khirdany, Elvin; Faisol, Faisol (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to determine the influence of content marketing on purchasing decisions for Glad2Glow skincare products on the TikTok Shop marketplace, with a case study of the people of Sampang Regency. In today's digital era, content marketing has become a marketing strategy widely used by businesses, especially in marketing products through social media. TikTok Shop, as a growing e-commerce platform, provides video content-based marketing features that are considered effective in building relationships with consumers. The research method used is a quantitative descriptive method. The type of data used in this study is quantitative data. The data sources used are primary and secondary data. The sampling technique used was purposive sampling with certain criteria, totaling 115 respondents. The results of the study indicate that content marketing has a positive and significant effect on purchasing decisions for Glad2Glow products on TikTok Shop. The more interesting, informative, and relevant the content presented, the greater the likelihood of consumers making a purchase. This proves that content-based marketing strategies have a significant role in influencing consumer behavior in the digital era.